Sporadic hyperekplexia due to self-limiting brainstem encephalopathy - Yilmaz D (Dove Medical Press, 2017)
Dilek Yilmaz,1 Bülent Cengiz2 1Department of Neurology, Konya Numune State Hospital, Konya, 2Department of Neurology, Gazi University Faculty of Medicine, Ankara, Turkey Abstract: Hyperekplexia is a rare movement disorder characterized by pathologically exaggerated response to unexpected stimuli. It is differentiated from the normal startle reflex by its lower threshold, higher intensity, and resistance to habituation. Many of the acquired hyperekplexias result from brainstem involvement such as encephalitis, infarct, hemorrhage, pontocerebellar hypoplasia and medullary compression. This case report depicts a rare manifestation of hyperekplexia. The unusual aspect of this case was the vocalization that was reproduced in response to startling stimuli. Startle induced vocalization is not a part of the classical hyperekplexia description. When faced with a patient with pathologically exaggerated response to unexpected stimuli, the physician should consider this rare condition in the differential diagnosis, and also keep in mind that the disease may present with features different from those listed in the textbooks. Keywords: hyperekplexia, startle, brainstem encephalopathy